Bottom-Up Resource and Cost Estimation for Restoration of Supply Chain Interdependent Critical Infrastructure. Issue 4 (2nd October 2021) - Ojha, Akhilesh; Long, Suzanna; Shoberg, Tom; Corns, Steven
Abstract: Extreme events can damage or destroy multiple supply chain interdependent critical infrastructures elements. Although much research has focused on developing efficient restoration strategies, and/or making critical infrastructures more resilient, practitioners need tools to determine resources necessary to restore such damage. The methodology developed in this research estimates both the resources required to support the repair personnel, and restore different infrastructure elements. This method uses a dynamic mathematical model that establishes a framework to estimate post-disaster restoration costs from a whole system perspective. The model is validated with a case study of the resources required to restore multiple infrastructures that were damaged by the EF-5 tornado that struck Joplin, Missouri on May 22, 2011. Engineering managers, city planners, and policy makers can use the methodologies developed in this research to develop effective disaster planning schemas and to prioritize post-disaster restoration operations.